Exploring Students' Mathematical Creative Thinking in the Context of Social Arithmetic - Dewi Indrapangastuti; Rokhmaniyah Rokhmaniyah; Wahyudi Wahyudi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mathematics education aims to develop students' logical and creative thinking skills, which are essential for solving complex and non-routine problems. Creativity in mathematics is particularly important for problem-solving and critical reasoning. This study analyzes students' mathematical creative thinking abilities in social arithmetic, focusing on fluency, flexibility, originality, and elaboration. This study employed a descriptive qualitative method with a case study approach to explore the complexity of mathematical creative thinking. The research involved 40 second-semester students from the Elementary School Teacher Education program at the Faculty of Teacher Education and Educational Sciences, UNS. Participants were categorized into high, medium, and low academic ability groups. Data collection techniques included a validated test instrument (assessed using the Aiken index), with reliability determined by Cronbach’s Alpha coefficient. Interviews were conducted to supplement the test results. Data analysis followed a process of data reduction, presentation, interpretation, and verification. The findings revealed that students’ mathematical creative thinking abilities varied by indicator: fluency (57.5%, moderately creative), flexibility (75%, creative), originality (60%, moderately creative), and elaboration (52.5%, moderately creative). The overall average score was 61.25%, categorizing students as creative. The dominant indicator was flexibility, which fell into the creative category. These results suggest that students demonstrate adaptability in problem-solving but may require further development in originality and elaboration. Students' mathematical creative thinking abilities are strongest in flexibility. It is recommended that mathematics educators implement innovative learning models to enhance technological, pedagogical, content knowledge (TPCK) and scientific reasoning.